Effects of different concentrations of ascorbic acid on the stability of (+) – Catechin under enzymatic conditions. (15th January 2023) - Li, Caiyun; Ding, Xuefeng; Li, Jie; Yan, Shoulei
Highlights: The enzymatic browning of catechin is the same as that of non-enzymatic browning. 1 mM AA had the most effective protective effect on catechin. The effect of AA on the stability of catechin is time-dependent and dose-dependent. The antioxidant effect of AA and the addition reaction of DHAA are two key factors affecting the stability of catechin. Abstract: A series of incubation systems of (+) - catechin (Cat), ascorbic acid (AA) and polyphenol oxidase (PPO) of lotus rhizome at 40 °C were performed to investigate the effect and oxidation pathway of AA on the stability of Cat. The results showed that after the enzymatic or non-enzymatic oxidation of Cat, the products of the two reactions were the same, namely epicatechin, catechin dimer and dehydrogenated catechin dimer. After adding AA, the protective effect of AA on catechin increased first and then decreased with the increase of AA concentration. 0.1 mmolL(exp)-1 AA can inhibit PPO activity in a short time. Within 24 h, 1 mmolL(exp)-1 AA can keep Cat content at 87.88 %. At the concentration of 10 mmolL(exp)-1 AA, excessive AA is oxidized to form a large amount of dehydroascorbic acid (DHAA), which forms an adduct with Cat, promoting the consumption of Cat. The effect of AA on the stability of Cat is time-dependent and dose-dependent.